Pemasaran Daya Tarik Wisata Mahagangga Valley di Desa Ababi Kabupaten Karangasem - Ni Putu Oka Wahyuni (Jurnal Mosaik Hospitaliti, 2026)
Mahagangga Valley of Ababi Village, Karangasem Regency is a tourist attraction which carry on the concept of nature-based tourism. Mahagangga Valley has a great potential to attract domestic tourist and foreigners who love nature. This study is aimed at knowing the marketing strategy done by the tourist attraction management of Mahagangga Valley and analyzing the marketing mix of Mahagangga Valley. The study used a qualitative descriptive method with data collection through observation, interviews, and documentation. The informants of this study are 50 respondents of questioner, the management of Mahagangga Valley, the employees, local communities of Ababi Village, and the visitors. The analysis technique is done through data reduction, data presentation, and conclusion based on the marketing strategy concept (Segmentation, Targeting, dan Positioning) and marketing mix of 7P (Product, Price, Place, Promotion, People, Process, dan Physical Evidence) to evaluate the applied strategy which are able to answer the market needs and support the growth of tourist attraction. The result of the study showed that Mahagangga Valley build the identity as the Eco and Culture Tourism. The promotion strategy is through the social media and team work with other tourism executant to reach the market. The pricing is based on the visitors’ experiences and services flexibly by involving the local communities as the employee. The finding of the study is the application of marketing mix can effectively improve the quality and tourism competitiveness.